Foliar fungi-imposed costs to plant productivity moderate shifts in composition of the rhizosphere microbiome - Lane, Brett R.; Kuhs, Molly A.; Zaret, Max M.; Song, Zewei; Borer, Elizabeth T.; Seabloom, Eric W.; Schlatter, Daniel C.; Kinkel, Linda L. (Frontiers in Plant Science, 2025)
Plants in grasslands navigate a complex landscape of interactions including competition for resources and defense against pathogens. Foliar fungi can suppress plant growth directly through pathogenic interactions, or indirectly via host growth-defense tradeoffs. The exclusion of foliar fungi allows the reallocation of resources from defense to growth and reproduction. In addition, plants also invest photosynthates in rhizodeposition, or root exudates, which play a significant role in shaping the rhizosphere microbial community. However, it remains unclear what impact the exclusion of foliar fungi has on the allocation of resources to rhizodeposition and the composition of the rhizosphere microbial community. Using a 6-year foliar fungicide study in plots planted with 16 species of native prairie plants, we asked whether foliar fungi influence the rhizosphere microbial composition of a common prairie grass (Andropogon gerardii) and a common legume (Lespedeza capatita). We found that foliar fungicide increased aboveground biomass and season-long plant production, but did not alter root biomass, seed production, or rhizosphere microbial diversity. The magnitude of change in aboveground season-long plant production was significantly associated with the magnitude of change in the rhizosphere microbial community in paired foliar fungicide-treated vs. control plots. These results suggest important coupling between foliar fungal infection and plant investment in rhizodeposition to modify the local soil microbial community.